Pelatihan Manajemen Waktu untuk Mengurangi Prokrastinasi Akademik pada Siswa SMK di Desa Sukamurni - Bunga Angel; Fajar Prihesnanto; Setyo Supratno; Novita Dian Iva Prestiana (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
Education plays a crucial role in improving human resource quality, yet academic procrastination remains a challenge, as seen in students at SMK Mekar Murni who tend to delay assignments, show a decline in academic performance, and struggle with time management. This community service program aims to enhance students' time management skills through delivering materials and discussions with 25 students from 11th and 12th grades in a participatory manner. The method used is a pre-experimental design with a one-group pre-test–post-test, employing a quantitative approach. Evaluation was carried out using a Time Management instrument consisting of three indicators: long-term time orientation, schedule management, and daily time management. The results show an average pre-test score of 48.00 (Standard Deviation = 4.99) with the majority of students in the moderate category. After the intervention, the post-test score increased to 83.4 (Standard Deviation = 7.37). The proportion of low category students increased from 4% to 68%, moderate category decreased from 56% to 24%, and high category increased from 40% to 8%. These findings indicate that time management training can reduce academic procrastination by enhancing students' understanding of effective time management.